Attention deficit disorder : the unfocused mind in children and adults - Brown, Thomas E., 1942- (New Haven : Yale University Press, 2005)
(Publishers Description) "Myths about Attention Deficit Disorder/Attention Deficit/Hyperactivity Disorder(ADD/ADHD) abound. This disorder frequently goes unrecognized, and even when diagnosed may be inadequately treated. In this up-to-date and clearly written book, a leading expert offers a new way of understanding ADD. Drawing on recent findings in neuroscience and a rich variety of case histories from his own clinical practice, Dr. Thomas E. Brown describes what ADD syndrome is, how it can be recognized at different ages, and how it can best be treated. This is the first book to address the perplexing question about ADD: how can individuals, some very bright, be chronically unable to pay attention, yet be able to focus very well on specific tasks that strongly interest them? Dr. Brown disputes the 'willpower' explanation and explains how inherited malfunctions of the brain's management system prevent some people from being able to deal adequately with challenging tasks of childhood, adolescence, and adulthood. His book is an authoritative and practical guide for physicians and psychologists, parents and teachers, and the 7 to 9 percent of persons who suffer from ADD/ADHD."
Misconceptions about focus and willpower -- Six aspects of a complex syndrome -- ADD syndrome and the working brain -- Childhood: struggling with self-management -- Adolescence: greater independence brings new challenges -- Adulthood: managing responsibilities, finding a niche -- How ADD syndrome differs from normal inattention -- Disorders that may accompany ADD syndrome -- Medications and other treatments -- Fears, prejudices, and realistic hope.
Includes bibliographical references (p. 323-348) and index.
Keywords: Attention-deficit hyperactivity disorder; Attention-deficit hyperactivity disorder in adults